2019
DOI: 10.1109/access.2019.2916578
|View full text |Cite
|
Sign up to set email alerts
|

FirstLife: Combining Social Networking and VGI to Create an Urban Coordination and Collaboration Platform

Abstract: Designing an urban platform intended to be a shared virtual space for coordination, cooperation, and collaboration among public administrations, local institutions, civic organizations, businesses, and citizens is an open challenge. This paper presents the current framework and applications of the civic social network FirstLife, developed following a participatory design approach and an agile methodology. The platform combines volunteered geographic information (VGI) with social networking functionalities. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
9
0
2
Order By: Relevance
“…Segundo os autores, nos resultados dos trabalhos levantados, foram observados uma maior aceitação, maior usabilidade e acessibilidade do sistema. Boella et al (2019) apresentam uma rede social cívica chamada FirstLife, que combina informação geográfica voluntária com funcionalidades de redes sociais. Baseados em informações geográficas de crowdsourcing os autores propõem uma estrutura digital para apoiar a coordenação, cooperação e colaboração entre os cidadãos e instituições públicas.…”
Section: Trabalhos Relacionadosunclassified
See 1 more Smart Citation
“…Segundo os autores, nos resultados dos trabalhos levantados, foram observados uma maior aceitação, maior usabilidade e acessibilidade do sistema. Boella et al (2019) apresentam uma rede social cívica chamada FirstLife, que combina informação geográfica voluntária com funcionalidades de redes sociais. Baseados em informações geográficas de crowdsourcing os autores propõem uma estrutura digital para apoiar a coordenação, cooperação e colaboração entre os cidadãos e instituições públicas.…”
Section: Trabalhos Relacionadosunclassified
“…O processo apresentado em Boella et al (2019), pode ser dividido em duas fases principais: a fase de laboratório e a fase de workshop. A fase de laboratório foi organizada para permitir que aqueles que participam efetivamente da vida urbana da cidade cooperassem para encontrar oportunidades e desafios para o desenvolvimento da plataforma.…”
Section: Trabalhos Relacionadosunclassified
“…The designed system is built on FirstLife [33], a civic social network based on a web-based platform that can be accessed by both desktop and mobile devices. The system allows the collection of data from users, integrating them with information coming from heterogeneous data sources (e.g., open data).…”
Section: Systemmentioning
confidence: 99%
“…This process is mainly carried out when the citizens use their smartphones and wearable devices, which usually have some type of embedded sensors, including an accelerometer, GPS, digital compass, environmental sensors, microphone, gyroscope, and camera (Wazny 2017). As previous research has shown, mobile phones have been unique in providing crowdsourced data for accomplishing the localization, labelling and mapping of events, personal and surrounding contexts, social relationships, and human activities (Annis & Nardi, 2019;Boella et al, 2019;Calabrese, Colonna, Lovisolo, Parata, & Ratti, 2011;Kong et al, 2019;Tong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%